Exploring the relationship between polio type 2 serum neutralizing antibodies and intestinal immunity using data from two randomized controlled trials of new bOPV-IPV immunization schedules. Issue 52 (19th December 2017) - Bandyopadhyay, Ananda S.; Asturias, Edwin J.; O'Ryan, Miguel; Oberste, M. Steven; Weldon, William; Clemens, Ralf; Rüttimann, Ricardo; Modlin, John F.; Gast, Chris
Highlights: Bivalent Oral Polio Vaccine (bOPV) without type 2 poliovirus has replaced trivalent OPV globally. Inactivated polio vaccine is now the only elective source of protection against type 2 poliovirus. We examined the relationship of humoral and intestinal type 2 immunity from new IPV-bOPV schedules. High neutralizing antibody titers were weakly associated with lower type 2 shedding. Abstract: Background: Inactivated polio vaccine (IPV) is now the only source of routine type 2 protection. The relationship, if any, between vaccine-induced type 2 humoral and intestinal immunity is poorly understood. Methods: Two clinical trials in five Latin American countries of mixed or sequential bOPV-IPV schedules in 1640 infants provided data on serum neutralizing antibodies (NAb) and intestinal immunity, assessed as viral shedding following oral mOPV2 challenge. Analyses with generalized additive and quantile regression models examined the relationships between prechallenge NAb titers and proportion, duration and titers (magnitude) of viral shedding. Results: We found a statistically significant (p < .0001) but weak relationship between NAb titer at the time of mOPV2 challenge and the Shedding Index Endpoint, the mean log10 stool viral titer over 4 post-challenge assessments. Day 28 post-challenge shedding was 13.4% (8.1%, 18.8%) lower and the Day 21 post-challenge median titer of shed virus was 3.10 log10 (2.21, 3.98) lower for subjects with NAb titers at the ULOQ as compared with LLOQ on day of challenge. Overall, there was a weak but significant negative relationship, with high NAb titers associated with lower rates of viral shedding, an effect supported by subset analysis to elucidate between-country differences. Conclusions: Taken alone, the weak association between pre-challenge NAb titers following IPV or mixed/sequential bOPV/IPV immunization and differences in intestinal immunity is insufficient to predict polio type 2 intestinal immunity; even very high titers may not preclude viral shedding. Further research is needed to identify predictive markers of intestinal immunity in the context of global OPV cessation and IPV-only immunization.